P–800 Generation of artificial oocytes by two distinct mechanisms. (6th August 2021) - Xie, P; Petrini, A; Trout, A; Rosenwaks, Z; Palermo, G
Abstract: Study question: Are haploid genome replication and somatic cell haploidization feasible mechanisms for generating parentally genotyped oocytes? Summary answer: Artificial oocytes can be generated by haploid genome replication and somatic cell haploidization. The latter is more efficient and capable of generating live offspring. What is known already: A low number of mature oocytes is one of the major limitations to treating infertile women who have impaired ovarian reserve. Although it has been proposed that competent oocytes can be created by a phenomenon known as somatic cell haploidization (SCH), its clinical value has yet to be examined due to its poorly understood mechanism. On the other hand, spindle transfer has been clinically applied for mitochondrial replacement therapy. Therefore, we propose to utilize G2-phase haploid pseudo-blastomere (HpB), generated by parthenogenesis, as a nuclear donor to create oocyte replica. Study design, size, duration: In the past 7 months, individual G0 phase cumulus cells (CCs) were transferred into 1, 066 ooplasts for SCH. HpBs obtained from the activation of 80 oocytes were transferred into 464 ooplasts. Both cohorts were ICSI-inseminated and placed in the time lapse for embryo development. Another 379 unmanipulated oocytes were ICSI-inseminated, serving as control. Pre-implantation development was monitored and compared for both neogametogenesis techniques. Fully expanded blastocysts were transferred to obtain live pups. Participants/materials, setting, methods: CCs were isolated from the cumulus oophorus of B6D2F1 mice. HpBs were obtained via oocyte activation, cultured to the 8-cell stage, and subsequently treated by nocodazole to synchronize at the G2-phase. In two experimental groups, CCs or HpBs were individually transferred into the perivitelline space of the ooplasts with inactivated Sendai virus. Reconstructed oocytes presenting with a pseudo-meiotic spindle were fertilized by piezo-actuated ICSI. Blastocysts were transferred into a pseudo-pregnant CD–1 surrogate to obtain pups. Main results and the role of chance: A total of 1, 769 oocytes underwent enucleation to generate ooplasts, with a survival rate of 97%. Survived ooplasts were allocated to SCH (n = 1, 034) and HpB-SCNT (n = 458). To generate HpBs, 80 unmanipulated oocytes were activated; 58 of them progressed to the 8-cell stage and generated 464 HpB for SCNT. For SCH, CCs were selected based on morphology with a diameter <10 micron. Nuclear transfer of CCs and HpB yielded survival rates of 98.6% and 93.2%, respectively. Following SCH and HpB-SCNT, spindle development for SCH and HpB-SCNT was comparable at 63.5% for SCH and 66.7% for HpB-SCNT. The ICSI survival rates for SCH and HpB-SCNT were 58.9% and 64.9%, respectively, but lower than the control at 73.9% (P < 0.001). Fertilization rates for SCH and HpB-SCNT were also comparable at 61.3% and 64.3%, respectively, but lower than the control at 89.6% (P < 0.00001). Full pre-implantation development was achieved for both experimental groups. While the SCH group yielded a development rate of 24.6% (n = 94), the HpB-SCNT group yielded a lower rate at 12.4% (n = 23) (P < 0.001), both lower than the control (71.7%, P < 0.00001); however, the morphokinetics of the embryo development was retained. To date, only 3 live pups were obtained from SCH group. Limitations, reasons for caution: While these techniques to manufacture oocytes are very new and highly experimental, our findings show a lower blastulation rate for oocytes generated by HpB. Both techniques require refinement and improvement of reliability and consistency before they can be considered a feasible technique for human reproduction. Wider implications of the findings: The study confirms the potential to create artificial oocytes capable of supporting full pre-implantation development and, in some cases, live pups. If further streamlining of both procedures demonstrates their safety, they may both represent a viable option to generate de novo gametes Trial registration number: N/A